2015
DOI: 10.3390/met5031732
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Mechanical Behavior of Super Duplex Stainless Steel with Sigma Precipitation

Abstract: Experimental studies in various aspects have to be conducted to maintain stable applications of super duplex stainless steels (SDSS) because the occurrence rate of sigma phase, variable temperature and growth direction of sigma phase can influence mechanical performances of SDSS. Tensile tests of precipitated SDSS were performed under various temperatures to analyze mechanical and morphological behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
4
9
0
8
Order By: Relevance
“…As the annealing temperature increases, the volume fraction of austenite decreases, and the ferrite must take up more nitrogen in the solid solution. Although these levels of nitrogen are soluble in ferrite at high temperatures, Cr2N precipitates in the ferrite upon rapid cooling because nitrogen is relatively High toughness can be obtained by implementing suitable solution temperatures and cooling rates [61][62][63]. This finding is consistent with a previous report [64] indicating that the optimal solution temperature and cooling rate result in high toughness.…”
Section: Precipitation Of Other Phasessupporting
confidence: 83%
See 1 more Smart Citation
“…As the annealing temperature increases, the volume fraction of austenite decreases, and the ferrite must take up more nitrogen in the solid solution. Although these levels of nitrogen are soluble in ferrite at high temperatures, Cr2N precipitates in the ferrite upon rapid cooling because nitrogen is relatively High toughness can be obtained by implementing suitable solution temperatures and cooling rates [61][62][63]. This finding is consistent with a previous report [64] indicating that the optimal solution temperature and cooling rate result in high toughness.…”
Section: Precipitation Of Other Phasessupporting
confidence: 83%
“…Moreover, such deposition can reduce the toughness of DSS and SDSS [56][57][58][59][60]. High toughness can be obtained by implementing suitable solution temperatures and cooling rates [61][62][63]. This finding is consistent with a previous report [64] indicating that the optimal solution temperature and cooling rate result in high toughness.…”
Section: Precipitation Of Other Phasessupporting
confidence: 82%
“…This creates very high stacking fault energies (SFE) which is higher than the bond energies holding the atoms together, causing brittleness [21]. Low plasticity (lower than 4%) was reported by Kim et al [28], where the mechanical behaviour of duplex stainless steel containing sigma precipitates were studied. Hau et al [29] investigated the sigma phase embrittlement and reported that the presence of sigma phase in stainless steel resulted in loss of ductility and toughness at room temperature.…”
Section: Metals 2018 8 X For Peer Review 4 Of 11mentioning
confidence: 99%
“…However, its main drawback is the tendency to form detrimental phases at temperatures between 600 • C and 900 • C, being the cause of a significant loss of toughness and resistance to localized corrosion. One of the most known and representative detrimental phases is the precipitation of the sigma phase (σ), a Cr-and Mo-rich intermetallic compound [12][13][14][15][16][17][18][19][20][21]. This σ phase shows a tetragonal crystallographic structure with 32 atoms per unit cell [22] making possible a considerable increase in the resultant hardness, whereas a decrease in the toughness as well as elongation is also observed [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%